Predictive modelling of mobile marketing usage among generation Y: a preliminary survey - Mohammad Ismail; Razli Che Razak; Mohd Rafi Yaacob; Mohd Nazri Zakaria; Nadia Hanum; Azyanee Luqman (2016)
This preliminary analysis examines mobile marketing usage among Generation Y. This study investigates the level of mobile marketing usage among Gen Y and to identify the relationships between attitude, subjective norm, perceived behavioural control, perceived risk, behavioural intention and actual usage. This study utilizes self-administered survey questionnaires by using 115 students from University Malaysia Kelantan. Overall, the results provides verification of a positive relationship between the constructs of attitude, subjective norm, perceived behavioural control and perceived risk on intention to use mobile marketing services.